2006
DOI: 10.1021/jp060072y
|View full text |Cite
|
Sign up to set email alerts
|

In Search of Excited-State Proton Transfer in the Lumichrome Dimer in the Solid State:  Theoretical and Experimental Approach

Abstract: Quantum chemical density functional theory (DFT) calculations and spectral data were employed to investigate the possibility of the excited-state double proton transfer (ESDPT) in lumichrome crystals. The calculations in a lumichrome dimer predict a transfer of a proton in the first excited state, leading to a cation-anion pair. The presently reported X-ray structure of 1,3-dimethyllumichrome and its complex solid-state luminescence indicate that also in this molecule intermolecular hydrogen bonds might be inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 62 publications
(110 reference statements)
0
11
0
Order By: Relevance
“…For example, we have demonstrated that interactions between parallel and antiparallel local dipoles are responsible for mutual orientation of oxalamide molecules [30], while the presence of a new type of a weak bond between oxygen atom from carbonyl moiety and carbon atom within aromatic ring governs the behavior of imidazopyridine derivatives [31]. Similarly, combined quantum mechanical and X-ray investigations appeared successful in studies on grid-type complexes [32] and double proton transfer in lumichrome dimers [33]. A series of computational and experimental studies allowed us to provide the reasons favoring conformations of drugs fulvastatin [34], azathioprine [35], and other purines [36], as well as (R,R)-tartaric acid esters [37], amides [38], nitriles [39], or deoxyfluoro derivatives [40].…”
Section: Introductionmentioning
confidence: 93%
“…For example, we have demonstrated that interactions between parallel and antiparallel local dipoles are responsible for mutual orientation of oxalamide molecules [30], while the presence of a new type of a weak bond between oxygen atom from carbonyl moiety and carbon atom within aromatic ring governs the behavior of imidazopyridine derivatives [31]. Similarly, combined quantum mechanical and X-ray investigations appeared successful in studies on grid-type complexes [32] and double proton transfer in lumichrome dimers [33]. A series of computational and experimental studies allowed us to provide the reasons favoring conformations of drugs fulvastatin [34], azathioprine [35], and other purines [36], as well as (R,R)-tartaric acid esters [37], amides [38], nitriles [39], or deoxyfluoro derivatives [40].…”
Section: Introductionmentioning
confidence: 93%
“…Such an interpretation is based on an analogy to the results of earlier studies of lumichrome using luminescence experiments, DFT calculations and X-ray results in ref. 30 and references cited therein. Note that this anion is believed to be deprotonated at N 1 position, thus the emission at 540 nm can be assigned to the N 3 anion.…”
Section: Room Temperature Laser-induced Phosphorescencementioning
confidence: 99%
“…As previously reported, alloxazine dimers are the origin of the isoalloxazine-type emission. 30,31 The published approximate dimensions of the intersections are 9 A ˚32 and, as Scheme 3 shows, the alloxazine dimer may fit into that cavity.…”
Section: Room Temperature Laser-induced Phosphorescencementioning
confidence: 99%
“…22,23 LCM is the major product of photodecomposition of riboavin (vitamin B 2 ) under neutral or acidic pH. Using quantum mechanical calculation, Sikorski et al 24 found an excited state double proton transfer (ESDPT) occurs in the LCM dimer in the solid state. A different type acid-base equilibrium of LCM at different pH values suggested the existence of different species LCM such as neutral species (DMAL and DMIS), two monoanions, and one dianion species.…”
Section: Introductionmentioning
confidence: 99%